The role of abiraterone in the management of metastatic castration-resistant prostate cancer. Issue 4 (April 2012) - Rawlinson, Alex; Mohammed, Aza; Beatty, John; Bell, Richard; Miller, Marek
Prostate cancer is the most common solid-organ cancer affecting the male population. Men with metastatic prostate cancer treated with androgen ablation therapy often respond rapidly, with improvement in bone pain and decreases in serum prostate-specific antigen. However, almost all patients progress to the castrate-resistant state and until recently chemotherapy was the only treatment available with proven survival benefit. Abiraterone is a new class of anti-androgen with proven survival benefit post-chemotherapy. In this review we discuss the characteristics of abiraterone and the clinical trials that led to its approval for the treatment of patients with prostate cancer.